2004
DOI: 10.1002/mus.20169
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid myopathy: Characteristic features of a still underdiagnosed disease

Abstract: A 62-year-old man with progressive proximal weakness underwent extensive evaluation including muscle biopsy without a clear diagnosis being established. A repeat muscle biopsy including Congo red-stained sections revealed infiltration of blood-vessel walls and endomysium with amyloid protein, as well as an unusual pattern of pathologic changes to muscle fibers. From a review of 79 cases of amyloid myopathy reported in the English-language literature, the characteristic features of this disorder are described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
70
0
11

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 35 publications
(122 reference statements)
5
70
0
11
Order By: Relevance
“…3,4 A small proportion of the patients (10%) had distal predominant weakness. 3 A case of amyloid myopathy presenting with distal weakness and atrophy of finger flexors has been described previously. 13 The second series 11 looking at the clinicopathological features of 16 patients with confirmed amyloid myopathy found that there was a frequent association with plasma cell dyscrasias.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…3,4 A small proportion of the patients (10%) had distal predominant weakness. 3 A case of amyloid myopathy presenting with distal weakness and atrophy of finger flexors has been described previously. 13 The second series 11 looking at the clinicopathological features of 16 patients with confirmed amyloid myopathy found that there was a frequent association with plasma cell dyscrasias.…”
Section: Discussionmentioning
confidence: 98%
“…Two series 3,11 reviewing the clinical and presenting features of patients with muscle weakness and biopsy evidence of amyloid deposition within skeletal muscle have been published. The larger of the two studies 3 reviewed 79 patients and found that proximal muscle weakness was the most common finding, present in 90% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Unlike these diseases, serum CK is often normal in patients with amyloidosis. 6 It is important to consider amyloidosis, in particular when serum CK is not elevated, for the patients whose muscles are hypertrophic without exercise.…”
mentioning
confidence: 99%